Does the junior IAAF athletic world championship represent a springboard for the success in the throwing events? A retrospective study - Piacentini, M. F.; Comotto, S.; Guerriero, A.; Bonato, M.; Vernillo, G.; La Torre, A. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The aim of the present study was to analyze how many finalists of the IAAF World Junior Championships (WJC) in the throwing events were present in the senior IAAF ranking at the end of 2012.